The decision to reimage following extravasation in diagnostic nuclear medicine - Kiser, Jackson W. (Frontiers in Nuclear Medicine, 2023)
The primary goal of diagnostic nuclear medicine is to provide complete and accurate reports without equivocation or disclaimers. If specific clinical questions cannot be answered because of radiopharmaceutical extravasation, the imaging study may have to be repeated. The decision to reimage is based on several factors including the diagnostic quality of the images, additional patient radiation dose, patient burden, and administrative constraints. Through process improvement efforts, nuclear medicine departments can significantly reduce the frequency of extravasation and thereby also the need for reimaging. Communication with the patient is important any time extravasation may impact their immediate or future care. The circumstances and potential ramifications should be explained, and patient concerns should be addressed. Although recent arguments have been made in favor of investigating and addressing only those extravasations which result in serious patient injury, patients and their referring physicians deserve to know any time their nuclear medicine study may have been impacted.